Resection and plasty in two patients with a neoplasm of great local extension - Aguiar, Alberto; Delgado, Bolívar; Lanza, Mario (Cirugía del Uruguay, 2020)
Two cases are presented of patients with neoplasms of great local extension (one of the neck and the other of the breast) that require a large local excision, followed by the corresponding plasty. It insists on the need of the oncologist surgeon to have knowledge and management of some elements of plastic and reconstructive surgery. Details of the techniques used in both cases are presented.